“MUSLIM’S LUMINAIRES FOR MUSLIM MOUNTAINEERS” – THE WORK OF MUSLIM AL-URADI ON “MUHAJIRISM” - Alibekov, Hizri Gadzievic (History, Archeology and Ethnography of the Caucasus, 2020)
The second half of the 19th century in the Caucasus marked the emergence of such a phenomenon as “muhajirism” – mass migration of Caucasians to the Ottoman Empire. This caused debates among Muslim theologians in the Caucasus. Having divided into supporters and opponents of “muhajirism”, theologians reflected their positions in written works. Among those theologians was Muslim al-Uradi (died in 1919), who described the said phenomenon in his work “Muslim’s luminaires for Muslim mountaineers”. The work provides positions of the both parties which allow us to thoroughly examine their views on social-political situation of that time and their considerations of “their place” in the new, changed reality. Muslim al-Uradi argues that there is no need for Dagestanis to move to other places and that “muhajirism” may affect negatively the religious life of Muslims of Dagestan.The author also considers some details related to the stay of Muslims under infidels’ authority, explains the basic rules of their interactions. Muslim al-Uradi tends to believe that Muslims of Dagestan can well live with non-believers in peace, be law-abiding tax-payers and at the same time remain true to their religion.The present article is devoted to the source-study analysis of the work by Muslim al-Uradi. The analysis of the said work allows to establish that the controversial popularity of “muhajirism” in the Russian Empire was not least due to the difference in views of the Hanafi and Shafi’i theological and legal schools on the resettlement of Muslims from territories that fell under the rule of non-Muslim countries.
Keywords: muhajirism; Hijra; jihad; dar al-kufr; dar al-islam; taquiya.